Whatever you are, be a good one : to get from good to great, you must learn how to get good - Emery, Stewart, 1941- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Success built to last: Creating a life that matters (ISBN: 9780132287517) by Jerry Porras, Stewart Emery, and Mark Thompson. Discover the power of becoming good at something you love to do!"--Resource description page.